Towards Understanding EFL Teachers’ Conceptions of Research: Findings From Argentina (2018)
This paper investigates the conceptions of research held by English as a foreign language teachers in Argentina. Quantitative data from 622 participants from an online questionnaire were followed by qualitative data from online interviews with 40 of those participants. Results show that the teachers conceptualised research through conventional notions closer to a quantitative paradigm. They felt research was not part of their job, and a lack of time was the main reason for not engaging in/with research. Teacher development, agency, empowerment, and autonomy could be sought by engaging teachers with forms of research which are meaningful to them, such as action research.